CNP regulates cardiac contractility and increases cGMP near both SERCA and TnI: difference from BNP visualized by targeted cGMP biosensors. Issue 6 (10th May 2021) - Manfra, Ornella; Calamera, Gaia; Froese, Alexander; Arunthavarajah, Dulasi; Surdo, Nicoletta C; Meier, Silja; Melleby, Arne Olav; Aasrum, Monica; Aronsen, Jan Magnus; Nikolaev, Viacheslav O; Zaccolo, Manuela; Moltzau, Lise Román; et al.
Abstract: Aims: Guanylyl cyclase-B (GC-B; natriuretic peptide receptor-B, NPR-B) stimulation by C-type natriuretic peptide (CNP) increases cGMP and causes a lusitropic and negative inotropic response in adult myocardium. These effects are not mimicked by NPR-A (GC-A) stimulation by brain natriuretic peptide (BNP), despite similar cGMP increase. More refined methods are needed to better understand the mechanisms of the differential cGMP signalling and compartmentation. The aim of this work was to measure cGMP near proteins involved in regulating contractility to understand compartmentation of cGMP signalling in adult cardiomyocytes. Methods and results: We constructed several fluorescence resonance energy transfer (FRET)-based biosensors for cGMP subcellularly targeted to phospholamban (PLB) and troponin I (TnI). CNP stimulation of adult rat cardiomyocytes increased cGMP near PLB and TnI, whereas BNP stimulation increased cGMP near PLB, but not TnI. The phosphodiesterases PDE2 and PDE3 constrained cGMP in both compartments. Local receptor stimulation aided by scanning ion conductance microscopy (SICM) combined with FRET revealed that CNP stimulation both in the t-tubules and on the cell crest increases cGMP similarly near both TnI and PLB. In ventricular strips, CNP stimulation, but not BNP, induced a lusitropic response, enhanced by inhibition of either PDE2 or PDE3, and a negative inotropic response. In cardiomyocytes from heart failure rats, CNP increased cGMP near PLB and TnI more pronounced than in cells from sham-operated animals. Conclusion: These targeted biosensors demonstrate that CNP, but not BNP, increases cGMP near TnI in addition to PLB, explaining how CNP, but not BNP, is able to induce lusitropic and negative inotropic responses. Graphical Abstract: